DEEP SEISMIC INVESTIGATION ACROSS THE BARENTS-KARA REGION AND NOVOZEMELSKIY FOLD BELT (ARCTIC SHELF) - Ivanova N.M.; Sakoulina T.S.; Roslov Yu.V. (My University, 2006)
Since 1995 SEVMORGEO has collected wide-angle reflection/refraction profiling (WARRP), multichannel seismic data (MCS) and seismoacoustic profiling, along regional lines 1-AR, 2-AR and 3-AR. These lines cross the whole Barents-Kara Region and Novozemelskiy Fold Belt. As a result, new geological data about the deep structure of the Earth's crust have become available. Four main tectono-stratigraphic units are distinguished in the section of the Earth's crust: (1) a sedimentary cover; (2) the Upper Proterozoic (mainly Riphean for the Barents Plate) and Riphean-Paleozoic (the South-Kara Syneclise) deformed and folded complexes; (3) the upper crystalline crust (granite-gneissic metamorphic Archean-Proterozoic complex); (4) the lower crust (basalt complex). The Barents-Kara Region is characterized by moderately thinned continental and subcontinental crust with an average thickness of 37-39 km. On islands and areas of uplifts with ancient massifs, the thickness of the crust (38-42 km)